SRC-2-mediated coactivation of anti-tumorigenic target genes suppresses MYC-induced liver cancer. - Shruthy Suresh; Deniz Durakoglugil; Xiaorong Zhou; Bokai Zhu; Sarah A Comerford; Chao Xing; Xian-Jin Xie; Brian York; Kathryn A O'Donnell (PLoS Genetics, 2017)
Hepatocellular carcinoma (HCC) is the fifth most common solid tumor in the world and the third leading cause of cancer-associated deaths. A Sleeping Beauty-mediated transposon mutagenesis screen previously identified mutations that cooperate with MYC to accelerate liver tumorigenesis. This revealed a tumor suppressor role for Steroid Receptor Coactivator 2/Nuclear Receptor Coactivator 2 (Src-2/Ncoa2) in liver cancer. In contrast, SRC-2 promotes survival and metastasis in prostate cancer cells, suggesting a tissue-specific and context-dependent role for SRC-2 in tumorigenesis. To determine if genetic loss of SRC-2 is sufficient to accelerate MYC-mediated liver tumorigenesis, we bred Src-2-/- mice with a MYC-induced liver tumor model and observed a significant increase in liver tumor burden. RNA sequencing of liver tumors and in vivo chromatin immunoprecipitation assays revealed a set of direct target genes that are bound by SRC-2 and exhibit downregulated expression in Src-2-/- liver tumors. We demonstrate that activation of SHP (Small Heterodimer Partner), DKK4 (Dickkopf-4), and CADM4 (Cell Adhesion Molecule 4) by SRC-2 suppresses tumorigenesis in vitro and in vivo. These studies suggest that SRC-2 may exhibit oncogenic or tumor suppressor activity depending on the target genes and nuclear receptors that are expressed in distinct tissues and illuminate the mechanisms of tumor suppression by SRC-2 in liver.